PEMANFAATAN MEDIA SOSIAL SEBAGAI STRATEGI PEMASARAN DIGITAL UMKM DI KECAMATAN RUMBAI KOTA PEKANBARU - Endah Wahyuningsih (Jurnal Ekonomi Bisnis Kompetif, 2025)
Cash waqf is an instrument of Islamic philanthropy that has great potential in supporting social welfare, education, health, and economic empowerment of the community. However, the optimization of cash waqf management is highly dependent on the role of the nazhir as the manager. This study aims to analyze the literacy level of cash waqf nazhir at the Indonesian Waqf Board (BWI) of Riau Province and analyze the ability to develop cash waqf assets nazhir at the Indonesian Waqf Board (BWI) of Riau Province. This study uses a quantitative descriptive approach with primary data obtained from 28 respondents who are nazhir at 12 cash waqf institutions officially registered with BWI Riau Province. Data analysis includes calculating the average score, assessment categories according to the theory of Chen & Volpe (1998), and descriptive analysis of each indicator. The results show that the literacy level of cash waqf nazhir is in the high category, with a percentage of basic knowledge of 84.88% and advanced knowledge of 84.38%. The majority of nazhir understand the basic concepts of cash waqf, Sharia law, the role of nazhir, and digital-based waqf regulations. Their ability to develop cash waqf assets is also high, as indicated by the percentage of asset development planning at 85.71%, asset development experience at 83.50%, and understanding of constraints and challenges at 83.04%. However, several obstacles remain, such as a lack of technical training, limited human resources, and minimal use of digital technology. Overall, the results of this study indicate that nazhir in Riau Province have good skills in cash waqf literacy and asset development